Ecosystem service research in the dry subtropics: Current state, temporal changes and drivers of regional variability - Aragón, Myriam Roxana (2024)
Dry subtropical (DST) regions that share similar climatic and topographic conditions exhibittoday significant disparities in population density, agricultural intensity, wealth and culturalvalues. In addition, they are also facing increasing pressures on their natural resources.These attributes collectively shape individuals´ varying dependence on natural resourcesand may influence their perception of ecosystem services (ES). In this study, we conducteda systematic literature review, focusing on the DST regions, to address two mainquestions: 1) What is the current state, temporal trends and regional variability in scientificresearch on ES and 2) What are the potential drivers of the variability in ES research?Amongst the 471 publications found in our review, 53% focused on provisioning services,followed nearly equally by cultural (33%) and regulating (30%) services. Only 13%addressed more than one ES category and approximately 33% mentioned economicvaluation. Our study reveals that research on ES in the dry subtropics experienced asignificant increase from 2005 onwards. Approximately 45% of the publications includedthe term ´ecosystem service´ and its frequency has risen substantially over time. Mostpublications primarily focus on African dry subtropics (over 60%), followed by South andNorth American ones. Publications from southern Asia and NE Australia were more scarce.Importantly, we found no clear relationship between the number of publications, publicationdensity or representativeness and the variables used as indicators of human pressure (e.g.population density). Consequently, research efforts in the DST regions appear to beinfluenced by a diverse range of financial and institutional constraints, internationalresearch agendas, as well as the personal interests of researchers, contributing to theidiosyncratic nature of this field.